ANALISIS FAKTOR FUNDAMENTAL TERHADAP HARGA SAHAM PADA PERUSAHAAN INFO BANK15 DI BURSA EFEK INDONESIA (Study Empiris Pada Perusahaan Bank Yang Terdaftar di BEI periode 2013-2017) - Anggi Pramudia Putri (INVENTORY: JURNAL AKUNTANSI, 2019)
The purpose of this study is to examine the effect of return on assets, return on equity, net profit margins, dividends per share, earnings per share of share prices at company Info Bank 15 listed on the Indonesia Stock Exchange period 2013-2017. This research uses quantitative methods with data secondary. The population in this study uses a purposive sampling method in company Info Bank 15 listed on the Indonesia Stock Exchange (IDX) during the 2013-2017 period. Based on the research results obtained that partially return on assets, return on equity, net profit margins, dividends per share and learning per share have no significant effect on price understanding.Keywords: return on assets, return on equity, net profit margin, dividend per share, earnings per share, price.